Sn-doped Bi1.1Sb0.9Te2S bulk crystal topological insulator with excellent properties - S. K. Kushwaha (Nature Portfolio, 2016)
An ideal topological insulator possesses an insulating bulk and a unique conducting surface however such behaviour is typically inhibited by bulk conduction due to defects. Here, the authors show that Sn-doped Bi1.1Sb0.9Te2S grown by the vertical Bridgman technique might overcome this hurdle.